A dança dos monstros: corpo e estética na arte e na Educação Física - Bezerra, Laise Tavares Padilha (2008)
The speeches about the body in interface with the technology, that fulfill the contemporary discussions, have been a stage of innumerable ethical, epistemological, aesthetic and ontological reflections. These happened bodies of the biotechnological scene also invade the dance, making several possible dialogues, making old concepts instable, opening way to revealing explorations and bringing with it implications and reflections. In this context, this research has as objective to discuss relations between body and technology in the dance; to understand the aesthetic configurations of the monster in the dance as possibility to question the body; to establish relations between the monstrous body in the dance and the conceptions of body in the Physical Education. We believe to be able to contribute for the reflection in the field of the Physical Education, since the work visualizes to extend the field of the discussions on aesthetic body and, as well as evidencing dialogues between different areas of the knowledge, as the Art and the Physical Education. From the point of view of the method, the work follows orientation of the Phenomenology for an aesthetic image appreciation of the videos in the choreographies In'perfeito and Violência of Cena 11, Dance Group that has marked new aesthetic configurations in the brazilian dance. Thus, we took for us the reflections on the "significant scenes" proposed by Bicudo (2000), to appreciate the dance of Cena 11. We emphasize that, after the identification of the Significant Scenes, it was necessary to approach these scenes from close senses, from which we detach the appearance, the space and the gesture. We evidence that, the bodies revealed by the group Cena 11, show an aesthetic that it interlaces the beauty, the ugly and the grotesque. An aesthetic of the unharmony, capable to transgress the oppositions, dialoguing with multiple antagonisms and that it amplifies the apollonian aesthetic linear rules, so predominant in the history of the dance and the Physical Education. We identify some indicatives that take us to the problematizations on an affective and anarchic body, when questioning the tyranny of the perfect corporality; the naturalization of the pain; the closed gesture in a finished and unique grammar; the standardization of feminine and masculine roles and the negation of the feeling. From these indicatives, we discuss the aesthetic of the deformed bodies of Cena 11, approaching it of the conceptions of body in the Physical Education, sometimes criticizing the rationalists and naturalistic views, sometimes dialoguing with more recent perspectives studied by researchers of this area of knowledge, which point to a reflection on the body under the optics of the sensible